Printmaking in British Columbia 1889-1983. (Victoria : Art Gallery of Greater Victoria, 1983)
Kuthan, George ; Anderson, D. ; Fanderlik, Velen ; Griffith, Julius ; Robinson, Clifford ; Amess, Fred ; Malloch, Joyce ; Irwin, Patricia ; Gaddes, Biddy ; Daglish, Peter ; Turner, Richard ; Steele, Robert ; Schmidt, Marianna ; Privett, Molly ; Binning, Bertram ; Bobak, Molly ; etc.
Printmaking in British Columbia 1889-1983, Art Gallery of Greater Victoria, Victoria, October 6 to November 27, 1983
Engels
kunstcatalogus
Keywords: British Columbia